Comparison of combination metformin-vildagliptin versus metformin-glimepiride in patients of type 2 diabetes mellitus with inadequately controlled metformin monotherapy - Deshkar, Anuradha T.; Gawali, Ujwala P. (International Journal of Research in Medical Sciences, 2022)
Background: Metformin has been recommended as a first-line therapy for T2DM in many guidelines. Adding a sulfonylurea to metformin has been a conventional and gold standard for decades to achieve tight glycaemic control. dipeptidyl peptidase-4 (DPP-4) inhibitors, an incretin-based therapy has emerged as important adjunctive drugs in T2DM. Therefore, the present study was planned to evaluate and compare the efficacy and safety of combination metformin-vildagliptin and metformin-glimepiride in patients of T2DM inadequately controlled with metformin monotherapy. Methods: A total 45 patients were allocated to each metformin-vildagliptin group and metformin-glimepiride group. Fasting plasma glucose, post prandial plasma glucose, body weight, adverse events were recorded at 0 week, 6 weeks, and 12 weeks. Glycosylated haemoglobin was recorded at 0 week and 12 weeks. Results: There was no statistically significant difference between the two groups (p>0.05) at the end of 12 weeks in the mean percentage reduction in FPG, PPPG and HbA1c.There was statistically highly significant (p<0.0001) difference between the two groups in mean percentage change in weight at the end of 12 weeks. Hypoglycemic events were significantly (p<0.05) more in metformin-glimepiride group. There was no statistically significant difference in the incidence of other adverse events between the two groups (p>0.05). Conclusions: In patients of T2DM with inadequately controlled metformin monotherapy, combination metformin-vildagliptin provides comparable efficacy in terms of FPG, PPPG and HbA1c to that of combination metformin-glimepiride with no risk of weight gain reduction in risk of hypoglycemic events.